Controlled growth of Bi-Functional La doped CeO2 nanorods for photocatalytic H2 production and supercapacitor applications. (22nd April 2022) - Nabi, Ghulam; Ali, Wajid; Majid, Abdul; Alharbi, Thamer; Saeed, Saba; Albedah, M.A.
Abstract: The rapid increase in energy consumption has severely rehabilitated human life urging to develop reliable and environmental friendly energy storage devices. Target oriented, systematic approach has been adopted to synthesis La doped CeO2 nanostructures with percentage as Lax Ce1-x O2 (X = 0, 1, 3, 5, 7) for potential super capacitors applications. Morphological doping impact on H2 production, electrochemical and optical properties are thoroughly investigated. XRD studies revealed the crystalline phase purity and attained approximately 35 nm average crystallite size. The SEM images exposed that primary morphology nano-particles has been tuned into nanorods by increasing the La concentration in CeO2 with size range 40∼60 nm. CV graphs depicted that the prepared electrodes obey the pseudo capacitive faradaic reactions behavior in nature. Maximum capacitance (925 F g -1 ) has been achieved by La0·05 Ce0·95 O2 which is better than numerous reported materials. The La0·05 Ce0·95 O2 also exhibited excellent GCD stability with 87.8% retention exhibiting it suitability for supercapacitor applications. Furthermore, the La0·05 Ce0·95 O2 showed the significantly higher H2 (9 μmol h −1 g −1 ) production rate as compared to undoped CeO2 and La0·01 Ce0·99 O2, La0·03 Ce0·97 O2 samples. This higher production is attributed to the recombination rate and have strong substantial correlation with optical characteristics. Graphical abstract: Image 1 Highlights: La doped CeO2 nanorods successfully synthesized by hydrothermal method. Specific capacitance 925 F g -1 has been achieved for La0·05 Ce0·95 O2 nanorods. More than 87% cyclic stability was achieved for La0·05 Ce0·95 O2 nanorods. The La0·05 Ce0·95 O2 showed the significantly H2 production rate (9 μmol h −1  g −1 ).